Spatial decision support for urban and environmental planning : a collection of case studies - Geneletti, Davide (IIUM Press, 2016)
In the last decade, planners around the world have begun to develop and use spatial decision support systems (SDSS) and planning support systems (PSS) in their professional work. These tools combine spatial and non-spatial data with models for determining the implications of alternative policy choices and visualisation tools for displaying results in easily understandable formats. This book presents a collection of case studies that illustrate the use of spatial information and GIS in combination with a number of decision support methods and techniques, such as multicriteria evaluation, linear programming, SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis, and simulation models. The case studies deal with a broad range of planning problems: strategic environmental assessment, urban povertymonitoring, protected area design, land use planning at municipal and national level, health risk assessment, and land suitability analysis. The chapters in this book bring together applications in very different contexts from Europe, Southeast Asia and Latin America, illustrating the power that today's decision and planning support tools are providing urban and environmental planners the world over. This book is essential reading for all students and researchers, as well as practitioners and decision makers, who are involved in and environmental planning and management.